Photo detection and modulation from 1,550 to 2,000 nm realized by GeSn/Ge multiple-quantum-well photodiode on 300-mm Si substrate - Zhou, Hao (2020)
A GeSn/Ge multiple-quantum-well (MQW) p-i-n photodiode structure was proposed for simultaneously realizing high detectivity photo detection with low dark current and effective optical modulation based on the quantum confined Stark (QCSE) effect. The MQW stacks were grown on a 300-mm Ge-buffered Si substrate using reduced pressure chemical vapor deposition (RPCVD). GeSn/Ge MQW p-i-n photodiodes with varying mesa diameters were fabricated and characterized. An ultralow dark current density of 16.3 mA/cm2 at -1 V was achieved as expected due to the low threading dislocation density (TDD) in pseudomorphic GeSn layer. Owing to the ultralow dark current density and high responsivity of 0.307 A/W, a high specific detectivity of 1.37×1010 cm·Hz1/2/W was accomplished at 1,550 nm, which is comparable with commercial Ge and extended-InGaAs photodetectors. Meanwhile, the bias voltage-dependent photo response was investigated from 1,700 to 2,200 nm. The extracted effective absorption coefficient of GeSn/Ge MQW shows a QCSE behavior with electric field-dependent exciton peaks from 0.688 to 0.690 eV. An absorption ratio of 1.81 under -2 V was achieved at 2 μm, which shows early promise for effective optical modulation. The high frequency response was calculated theoretically, and the predicted 3-dB bandwidth for the photodiode with a mesa diameter of 30 μm could reach 12 GHz at -2 V.